KAJIAN EFEKTIFITAS PENGGUNAAN TANAMAN ECENG GONDOK (Eichornia crassipes) DALAM MENURUNKAN BEBAN PENCEMAR AIR LIMBAH INDUSTRI GULA TEBU - Hasanudin, Udin; Suroso, Erdi; -, Hartono (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
Sugarcane industries produce wastewater with high levels of pollution load. Wastewater pollutant load can be lowered by treating wastewater in the WWTP. Wastewater treatment process using Biological conventional system still has the disadvantage of increasing the pH of the waste water at a given time. It causes algae blooming. Algae population levels increases due to nutrients in wastewater. To prevent algae Â from blooming, nutrient concentration in the waste water should be reduced. This study was aimed to measure the effectiveness of Waterhyacinth in lowering pollutant load of sugar cane industrial wastewater. The method used was to plant Waterhyacinth in aeration pond number 2 of WWTP and then taking samples at four locations and consists of point I (inlet pond aeration 2), point A (before the water hyacinth plant), point B (after the water hyacinth plant), the point C (waste pond outlet monitor). Parameters measured included pH, TSS, COD, NH4, and NO3. The result showed the wastewater treatment system using water hyacinth plant reduced the pollutant load sugar cane industrial wastewater at the rate of Â 0,000858%/m2 day, 0,010997%/m2 day, 0,008691%/m2 day, 0,005936%/m2 day, and 0,015016%/m2 day, respectively. These conditions indicate planting hyacinth was effective in lowering the level of industrial wastewater pollutant load of sugar cane. Keywords: algae bloom, sugarcane industry wastewater, waterhyacinth